2017
DOI: 10.1007/s41782-017-0015-8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-Emergent Central Sleep Apnea (Complex Sleep Apnea)

Abstract: Treatment-emergent central sleep apnea (TECSA) is a distinct form of sleep-disordered breathing characterized by the development of central sleep apnea during the initiation of positive airway pressure (PAP) therapy in patients with obstructive sleep apnea. The exact mechanisms of TECSA are not clearly known; however, several theories have been proposed. Usually, TECSA is transient and self-limited, and disappears after continued PAP use. Nevertheless, patients with persistent TECSA have lower adherence to PAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Since sleep problems, such as OSA and EDS, have been associated with the current coronavirus disease 2019 (COVID-19) pandemic [ 69 , 70 ], post-COVID-19 fatigue should be ruled out as well. Also, treatment-emergent central sleep apnea should be considered as a cause of persistent sleepiness since it can develop during treatment of OSA with CPAP and is also associated with EDS [ 71 ].…”
Section: Management Of Reds Due To Osamentioning
confidence: 99%
“…Since sleep problems, such as OSA and EDS, have been associated with the current coronavirus disease 2019 (COVID-19) pandemic [ 69 , 70 ], post-COVID-19 fatigue should be ruled out as well. Also, treatment-emergent central sleep apnea should be considered as a cause of persistent sleepiness since it can develop during treatment of OSA with CPAP and is also associated with EDS [ 71 ].…”
Section: Management Of Reds Due To Osamentioning
confidence: 99%
“…We might have been unable to completely differentiate between TECSA and non-pathological CSA-CSB observed at sleep onset or in the rapid eye movement (REM) stage in elderly patients and others. Although there are various reports on the incidence of TECSA during the early phase of positive airway pressure (PAP) treatment, TECSA is self-limiting and resolves within 3 months in 90% or more of patients [ 30 ]. In a prospective study of patients with normal BNP levels, Westhoff et al reported that the incidence of TECSA was as low as 0.56% [ 31 ].…”
Section: Discussionmentioning
confidence: 99%